1994
DOI: 10.1007/bf00053049
|View full text |Cite
|
Sign up to set email alerts
|

Response of wild lentil to Ascochyta fabae f.sp. lentis from Syria

Abstract: Ascochyta blight induced by Ascochyta fabae f.sp . lentis is a major foliar disease affecting lentil . Screening 241 accessions of the ICARDA wild lentil germplasm collection for resistance to a Syrian isolate of this fungus was conducted under artificial inoculation in a plastic house . The reaction of resistant accessions was confirmed in a second trial . Twenty-four out of 16 accessions of Lens culinaris ssp . orientalis were resistant, as were 12 of 35 accessions of L . culinaris ssp . odemensis, 3 of 35 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
2
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 8 publications
(3 reference statements)
2
43
2
1
Order By: Relevance
“…The wild Lens taxa are known to possess resistance to biotic and abiotic stresses (Bayaa et al, 1994(Bayaa et al, , 1995Gupta and Sharma, 2006). Incorporation of diverse genetic material from wild relatives using intensive hybridization would make it possible to recreate some of the lost variability while still respecting productivity and other desirable traits in lentil.…”
Section: Wild Relatives As a Source Of Novelmentioning
confidence: 99%
“…The wild Lens taxa are known to possess resistance to biotic and abiotic stresses (Bayaa et al, 1994(Bayaa et al, , 1995Gupta and Sharma, 2006). Incorporation of diverse genetic material from wild relatives using intensive hybridization would make it possible to recreate some of the lost variability while still respecting productivity and other desirable traits in lentil.…”
Section: Wild Relatives As a Source Of Novelmentioning
confidence: 99%
“…Whereas severe Ascochyta blight infection in chickpea is devastating, effects of the disease in lentil and pea are less conspicuous. Although substantial yield losses may occur in pea and lentil, complete destruction of the plants is uncommon even under severe epidemics (Gossen and Morrall 1983;Bayaa et al 1992;Ali et al 1994;Tivoli et al 1996;Morrall 1997). Thus, lentil and pea could have been sown in the winter, survived Ascochyta blight epidemics, and produced at least some yield.…”
Section: Epidemiological Considerationsmentioning
confidence: 99%
“…Resistance to Ascochyta blight, screening techniques, and breeding methods have been reported (Bayaa et al 1994 ;Ye et al 2002 ;Muehlbauer and Chen 2007 ;Tivoli et al 2006 ). The genetic control of Ascochyta blight resistance was described to be monogenic recessive in spite of having observed transgressive segregations (Tay and Slinkard 1989 ).…”
Section: Biotic Stressesmentioning
confidence: 97%
“…However, no commercial tetraploid lentil varieties have so far been released. (Bayaa et al 1994 ). Ye et al ( 2002 ) listed a series of cultivated and wild lentil materials as sources of partial resistance to Ascochyta blight, and Muehlbauer and Chen ( 2007 ) reported that the most prominent among the partially resistant germplasm accessions consisted of lentil accessions PI 339283, PI 374118, ILL5588, ILL5684, PR86-360, and ILL7537.…”
Section: Germplasm Collectionmentioning
confidence: 99%